Introduction to Cybersecurity for Teachers and Students in Indonesia in the Digital Era (Pengenalan Keamanan Siber bagi Guru dan Siswa di Indonesia di Era Digital) - Octiva, Cut Susan; Rahayu, Novi; Laia, Mitranikasih; Suryadi, Dikky; Hakim, Muhammad Lukman (UKInstitute, 2025)
This Community Service (PKM) activity aims to increase cybersecurity literacy among teachers and students as part of efforts to support digital transformation in education. The training was conducted online with an interactive approach, involving 50 participants from various schools in Indonesia. The material includes an introduction to cyber threats, mitigation strategies, and daily digital security practices. The evaluation was done through pre-test and post-test, accompanied by a participant satisfaction questionnaire. The results showed a significant improvement in participants' understanding, with an average score increase of 73%. The level of satisfaction of participants with the training reached the